This is Not a Revolution: The Sectarian Subject's Alternative in Postwar Lebanon - El Richani, Diana (Université d'Ottawa / University of Ottawa, 2017)
The 2015 trash crisis in Lebanon resulted in the emergence of movements centered on rights and the state’s responsibility. The protests and outrage were about an entire political structure that had allowed for such a failure in infrastructure to come into existence. After numbers on the street began to fade, the alternative discourses transitioned from the streets to the May 2016 Beirut municipality elections. My research explores how these actors relate to the state as citizens (a term they themselves use) within a political structure that perpetuates a kind of sectarian citizenship, and asks what being a citizen means in such a failed state, and how alternative fronts can push for a reconceptualization of citizenship, on a backdrop of neoliberalism.
Keywords: Social movements; Lebanon; Political Anthropology; Infrastucture; Citizenship; Sectarianism; State; Street Mobilizations